Identifying English Language Learning Needs of Hoteliers in a Five-Star Hotel in Jakarta - Dendeng, Keesha Nathania; Xenia, Tia (Jayapangus Press, 2025)
The need for English proficiency in the hospitality industry has become urgent due to the increasing number of international guests visiting Indonesia for many different purposes business, tourism, and education. In English for Specific Purposes (ESP) courses, a needs analysis is essential for instructors to provide their students with the specific language skills they need for their respective jobs. Therefore, this study aimed to investigate the needs of hoteliers at a five-star hotel in Jakarta through a semi-structured interview with the English teacher at the hotel as the representative of the Learning and Development (L&D) team. The interview result showed that the hoteliers, especially the Food & Beverage and the Culinary department, urgently needed to improve their English proficiency to communicate with guests and foreign co-workers since they still lacked speaking and listening skills in English. The hoteliers also had a low level of confidence and difficulty in developing ideas. This can be seen from how they tended not to speak much when using the English language. The interview results were transcribed and coded into four categories: necessities, wants, lacks, and learning needs. The results can be taken into consideration for future studies, which involve designing and developing an ESP module specifically tailored for hoteliers.